Basin Sediments Geometry and Strength as Controls for Post‐Failure Emplacement Style of Alpine Sub‐Lacustrine Landslides. Issue 10 (21st October 2022) - Klein, B.; Puzrin, A. M.; Stoecklin, A.; Kopf, A.
Abstract: Predicting the evolution of underwater mass movements in their post‐failure stage is vital for risk assessment of offshore structures and ensuring safety of coastal communities threatened by tsunami waves. In the absence of sedimentological and geotechnical data, variability of the post‐failure behavior in a specific marine or lacustrine setting is often attributed to predisposition factors such as the slope height‐drop and depth to the basal shear surface. In this paper, the contribution of other geometrical parameters such as the slope inclination and the relative thickness of the frontal basin sediments is investigated using a coupled Eulerian‐Lagrangian finite element framework. An emphasis is given to the important role of the strength difference between the slope and frontal basin sediments. The suggested framework is first validated against the well‐documented Zinnen slide in Lake Lucerne (Switzerland), successfully reproducing the post‐failure geometry and capturing the main features observed in published seismic profiles. It is then applied in a parametric study to illustrate the decisive role of the frontal basin sediments in determining the post‐failure geometry of underwater mass wasting in similar settings. Plain Language Summary: Submarine and sub‐lacustrine landslides that are sufficiently mobile to ramp out of their basal shear surface and override the seafloor over considerable distances may be responsible for tsunami waves generation. Alternatively, when confined, these landslides can still inflict significant damage on offshore infrastructure such as underwater cables breakage and destruction of offshore structures' foundation systems. To mitigate those risks, predicting the failure mechanism type and understanding its controls is crucial. In this paper, we present a finite element framework for simulating the post‐failure evolution of landslides and apply it to analyze the Zinnen landslide that took place in Lake Lucerne, central Switzerland, around the year 1601. After confirming that our framework can reproduce the observed post‐failure geometry, we use it to improve our understanding of different factors affecting the landslide dynamics and kinematics. We demonstrate, that besides the widely accepted controls such as slope height‐drop and depth to basal shear surface, other (mostly overlooked) factors may have a decisive effect on the post‐failure landslide evolution. These include the slope angle, the thickness of the frontal basin sediments and most importantly the difference in shear resistance between the slope and the frontal basin sediments. Key Points: The proposed CEL FEM framework successfully reproduces the post‐failure geometry of the Zinnen slide in Lake Lucerne, Switzerland Slope inclination, basin sediments' thickness and strength are key controls for post‐failure evolution of sub‐lacustrine landslides Accurately modeling the basin sediments strength and geometry is crucial for prediction of post‐failure geometry of landslide events